Pengaruh Brand Personality dan Brand Image Terhadap Brand Loyalty yang Dimediasi oleh Brand Trust pada Konsumen Sepatu Olahraga Merek Nike di Kota Bandung - Rio Sahrul Herdiansyah; Hariyadi Triwahyu Putra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to test the influence of brand personality and brand image on brand loyalty mediated by brand trust in consumers of Nike brand sports shoes in Bandung City. By using a quantitative approach with data obtained through a questionnaire to 120 users of Nike brand sports shoes in Bandung City who were selected using convenience sampling techniques with cross-sectional or one shot studies in obtaining data. The research instrument has been stated as reliable and valid. Data were analyzed using SPSS Statistics 27. Brand personality and brand image were found to have a positive and significant influence on brand loyalty through brand trust. The results of this study are expected to provide benefits for further research and to Nike sports shoe product managers regarding the design of appropriate strategies for increasing these loyalty attributes. Further researchers suggest exploring other factors that can strengthen brand loyalty.